BENTUK PENYELESAIAN SENGKETA PROSES PEMILIHAN UMUM - P. Ekon, Yanto M; Van Frits Kapitan , Rian; C Mau, Ellon B. (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM IBLAM), 2023)
The problem in this paper is what is the form of dispute resolution in the general election process? Meanwhile, the aim of this writing is to determine the form of dispute resolution in the general election process. The research methods used in this paper are the case approach method, conceptual approach method and statutory approach method. The results and discussion in this paper show that the forms of process disputes in general elections are divided into two. The first is a dispute between election participants and the second is a dispute between election participants and election organizers. The conclusions obtained by the authors regarding the form of dispute resolution in the general election process are: .1. the form of dispute resolution in the general election process between general election participants is resolved through Bawaslu; 2. The form of dispute resolution in the general election process between general election participants and general election organizers is resolved through Bawaslu through the mediation and adjudication stages as well as submitting a lawsuit to the State Administrative Court.